Ayam Peasant Sebagai Sumber Ide Penciptaan Batik Tulis Pada Kain Bemberg - Melati, Asri Yanti Sekar (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Pheasant Chicken is a poultry that comes from China, long tail and beautiful color are the main attraction, the price of Pheasant Chicken is quite high, but there are also many collectors from Indonesia who already have the chicken. The existence of Pheasant Chicken is an inspiration to develop and fulfill batik motifs for Pheasant Chicken fans. Many who like pheasant-themed batik make batik in demand, and many consumers want it. The increasing consumer interest in the Pheasant chicken motif has made the craftsmen passionate about producing the batik motif. The main stages involved are the processes of exploration, design, and realization. The exploration stage involves activities to explore sources of ideas through the steps of investigation and problem identification. The design stage is based on key points from the analysis, followed by the visualization of ideas expressed in various alternative forms to select the best option to be used as a reference for realization, and finally, the realization stage where the work is brought to life. The written batik technique is collaborated with the granitan technique for the main motif. This batik is produced using bemberg material to add selling value and quality to the product. The result of this creation includes six types of designs, with two of them being visualized into ready-to-wear fabric. The market segmentation is targeted at adult men and women